PENGARUH PELAYANAN PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA MEDAN BARAT - Asianna Martini Simarmata; Tri wulandsari (Mount Hope Economic Global Journal, 2024)
This study aims to determine the Influence of Tax Service Quality and Tax Sanctions toward Taxpayer Compliance at West Medan Tax Service Office. This research is based on quantitative data type and the data source is from primary data. The unit analysis and observation in this study is Individual Taxpayers at West Medan Tax Service Office, with total population of 30.346 taxpayers. From this population, 99 individual taxpayers registered in West Medan Tax Service Office are counted by slovin technique and chosen by accidental sampling technique. The method of analysis used in this study is multiple linear regression analysis which the regression equation is Taxpayer Compliance = 23,252 + 0,402 Tax Service Quality + 0,291 Tax Sanctions + e. Researcher used a significant level of 5%. The result of partial research shows that the Tax Service Quality has value tcount > ttable which is 5,357 > 1.98472 and significant value < 0,05 which is 0,000 < 0,05, Tax Sanctions has value tcount > ttable which is 2,735 > 1.98472 and significant value < 0,05 which is 0,007 < 0,05. The result of simultaneous research shows that Tax Service Quality and Tax Sanctions has value Fcount > Ftable which is 41,408 > 3,09 and significant value < 0,05 which is 0,000 < 0,05. The coefficient of determination (R2) is 0,463 or 46,3% which means that Taxpayer Compliance can be explained by the Tax Service Quality and Tax Sanctions. While the remaining 53,7% of Taxpayer Compliance can only be explained by other variables which was not